Improved brain functional network in major depressive disorder with suicidal ideation after individual target-transcranial magnetic stimulation treatment: a graph-theory analysis - Zhang, Yao; Mu, Nan; Qi, Shun; Sun, Chuanzhu; Rao, Yang; Yang, Xinyi; Guo, Jianying; Mu, Yunfeng (Frontiers in Psychiatry, 2025)
IntroductionMajor depressive disorder with suicidal ideation (MDD/SI+) is characterized by high prevalence, high recurrence rate, high disability rate and low response rate. There is an urgent need for clarifying the pathogenesis and developing novel treatment methods.MethodsSubjects were recruited for the collection of Magnetic Resonance Imaging data and clinical scales. Individual target-transcranial magnetic stimulation (IT-TMS) using Stanford Neuromodulation Therapy over individualized left dorsolateral prefrontal cortex was performed to treat MDD/SI+ with the ethical approval (KY20212218-C-1). GRETNA software was used to analyze brain network characteristics according to graph theory.ResultsA total of 32 patients (aged 18-55) and 28 healthy controls (aged 20-51) had been recruited. Patients after IT-TMS treatment had significant reduction in suicidal ideation and depressive symptom. The functional network of all three groups conformed to small-world topology. There was a renormalization in topology structure after IT-TMS treatment. Decreased functional connectivity between right insula and left anterior cingulate gyrus correlated with improvement in Beck Scale for Suicide Ideation scores.DiscussionThe current study highlights that MDD/SI+ patients in this cohort showed abnormal brain network connections compared to healthy controls, and that IT-TMS may exert its treatment effects by reducing spontaneous hyper-connectivity in the salience network and insula.